The diversity of bird species in Parit Tinggi and Beting, Kuala Pilah, Negeri Sembilan / Nurliyana Hashim - Hashim, Nurliyana (2017)
Birds play an important role in ecosystem as many plants depends on birds to spread their seeds for pollination and they are also important for insect control as they can consume large quantities of mosquitoes, caterpillars, beetles and moths. However, due to some activities such as housing construction, agriculture and logging can cause changes in bird species diversity. The aim for this study was to compare the diversity of bird species at three different sites and frequency of occurrence of birds at three different types of area in Parit Tinggi and Beting, Kuala Pilah. Mist net was used to capture birds and identify bird species at three different sites. After the observation birds were marked and release at the same place where they were captured. In this study, results showed Area 3 has more species compared to Area 1 and Area 2 as shown by the diversity index value (H’= 1.792) at Area 3 with frequency of occurrence of 6 bird species.